2013
DOI: 10.1017/s1047951113000401
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus prophylaxis in children with cardiac disease: a retrospective single-centre study

Abstract: Overall, 185 infants ≤ 2 years with haemodynamically significant cardiac disease received prophylaxis. In all, six qualifying infants missed immunisation and were hospitalised. Breakthrough respiratory syncytial virus infections occurred in 2.2%, demonstrating good efficacy of palivizumab in this population compared with the original, multi-centre, randomised trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Length of stay in hospital and ICU admissions vary among studies, but, on average, children with CHD and severe RSV infection spent an average of 4.4–14 days in hospital [5, 6, 8, 10, 27, 30, 33, 3840, 42, 45, 47, 48, 52]. Up to 53% were admitted to ICU with a median stay of 9.5–11 days [5, 6, 10, 27, 30, 44]. A retrospective, single-center study of 30 children with CHD and severe RSV infection reported that more than half (53.3%) were admitted to PICU for treatment [6].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Length of stay in hospital and ICU admissions vary among studies, but, on average, children with CHD and severe RSV infection spent an average of 4.4–14 days in hospital [5, 6, 8, 10, 27, 30, 33, 3840, 42, 45, 47, 48, 52]. Up to 53% were admitted to ICU with a median stay of 9.5–11 days [5, 6, 10, 27, 30, 44]. A retrospective, single-center study of 30 children with CHD and severe RSV infection reported that more than half (53.3%) were admitted to PICU for treatment [6].…”
Section: Resultsmentioning
confidence: 99%
“…Up to 53% were admitted to ICU with a median stay of 9.5–11 days [5, 6, 10, 27, 30, 44]. A retrospective, single-center study of 30 children with CHD and severe RSV infection reported that more than half (53.3%) were admitted to PICU for treatment [6]. The majority (87.5%) of PICU admissions were in infants ≤2 years of age and the median number of days spent in PICU was 11 days (range 1–43 days).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations